ПРАВИЛА И РЕКОМЕНДАЦИИ ДЛЯ АВТОРОВ - Кудряшов, О. І. (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2014)
Правила и рекомендации для авторов при оформлении статьи.